2012
DOI: 10.1073/pnas.1119226109
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous restriction is a cellular defense strategy that confers fitness advantage to bacteria

Abstract: Most bacterial genomes harbor restriction–modification systems, encoding a REase and its cognate MTase. On attack by a foreign DNA, the REase recognizes it as nonself and subjects it to restriction. Should REases be highly specific for targeting the invading foreign DNA? It is often considered to be the case. However, when bacteria harboring a promiscuous or high-fidelity variant of the REase were challenged with bacteriophages, fitness was maximal under conditions of catalytic promiscuity. We also delineate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Relaxed specificity could be typical to evolutionary intermediates whereby the methylase diverges beyond the coverage of its cognate restriction enzyme. However, contrary to the current dogma of absolute specificity, broad specificity of the restriction enzyme may provide more efficient protection, as recently shown for phage defense by KpnI nuclease (41). The specificity of action of the restriction–methylation system has implications beyond foreign DNA.…”
Section: Discussionmentioning
confidence: 79%
“…Relaxed specificity could be typical to evolutionary intermediates whereby the methylase diverges beyond the coverage of its cognate restriction enzyme. However, contrary to the current dogma of absolute specificity, broad specificity of the restriction enzyme may provide more efficient protection, as recently shown for phage defense by KpnI nuclease (41). The specificity of action of the restriction–methylation system has implications beyond foreign DNA.…”
Section: Discussionmentioning
confidence: 79%
“…NAPs have been shown to occlude and affect binding of TFs and other DNA binding proteins, such as restriction endonucleases and DNA methylation enzymes, suggesting a general role of NAPs in regulating genome accessibility by bending, wrapping and bridging the DNA structure [7], [12], [13], [27], [42], [76], [80], [81]. Additionally, NAPs influence DNA supercoiling, which has been shown to affect binding of the TFs Fis and OmpR in S. enterica [82], [83], providing another mechanism by which NAPs can change the chromosomal structure to influence TF-DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic promiscuity exhibited by the enzyme under in vivo conditions suggests a functional role. Studies carried out with R.KpnI revealed that retaining broad specificity in DNA cleavage characteristics provided a selective advantage to the host by better targeting foreign invading genetic elements (145). It is possible that a relaxed specificity of REases might also serve a hithertounknown function(s) in the organism.…”
Section: Promiscuity In Cofactor Utilization and Substrate Specificitymentioning
confidence: 99%